Cellular distribution of lipid A and LPS R595 after in vitro application to isolated human monocytes by freeze-fracture replica immunogold-labelling. Issue 6 (December 2013) - Richter, Walter; Heinbockel, Lena; Kaconis, Yani; Steiniger, Frank; Gutsmann, Thomas; Brade, Lore; Brandenburg, Klaus
We have performed freeze-fracture replica immunogold labelling of endotoxin preparations (lipid A and deep rough mutant LPS Re from Salmonella enterica sv. Minnesota), i.e. adding the endotoxins to human monocytes, labelling with monoclonal Abs recognizing either lipid A or LPS Re (A6 and A20 respectively), and fixing with immunogold secondary Ab. We have found that the endotoxins intercalated into the cell membranes with subsequent internalization by the cells. Surprisingly, membrane uptake took place only in the inner, plasmic leaflet of the plasma membrane, but there was no uptake of the outer leaflet for both compounds. Remarkable labelling could be also found for the two membranes of the nuclear envelope—in the case of lipid A only at the plasmic leaflet, but in the case of LPS Re on both leaflets. Isothermal calorimetric titration of the AB A20 with LPS and phospholipids showed that the Ab may bind not only to LPS but also to negatively charged phosphatidylserine. These results are discussed in the frame of the published concepts of cell activation induced by the endotoxins, i.e. how they are able to cause a conformational change of signalling proteins, such as the TLR4/MD2 complex.